Discontinuation of the liposomal delivery of bupivacaine has no effect on pain management after primary total knee arthroplasty: no effect on pain scores, opioid consumption, or functional status. (1st June 2021) - Feng, James E.; Ikwuazom, Chibuokem P.; Mahure, Siddharth A.; Waren, Daniel P.; Slover, James D.; Schwarzkopf, Ran S.; Long, William J.; Macaulay, William B.
Abstract : Aims: Liposomal bupivacaine (LB) as part of a periarticular injection protocol continues to be a highly debated topic in total knee arthroplasty (TKA). We evaluated the effect of discontinuing the use of LB in a periarticular protocol on immediate postoperative pain scores, opioid consumption, and objective functional outcomes. Methods: On 1 July 2019, we discontinued the use of intraoperative LB as part of a periarticular injection protocol. A consecutive group of patients who received LB as part of the protocol (Protocol 1) and a subsequent group who did not (Protocol 2) were compared. All patients received the same opioid-sparing protocol. Verbal rating scale (VRS) pain scores were collected from our electronic data warehouse and averaged per patient per 12-hour interval. Events relating to the opiate administration were derived as morphine milligram equivalences (MMEs) per patient per 24-hour interval. The Activity Measure for Post-Acute Care (AM-PAC) tool was used to assess the immediate postoperative function. Results: A total of 888 patients received Protocol 1 and while 789 received Protocol 2. The mean age of the patients was significantly higher in those who did not receive LB (66.80 vs 65.57 years, p = 0.006). The sex, BMI, American Society of Anesthesiologists physical status score, race, smoking status, marital status, operating time, length of stay, and discharge disposition were similar in the two groups. Compared with the LB group, discontinuing LB showed no significant difference in postoperative VRS pain scores up to 72 hours (p > 0.05), opioid administration up to 96 hours (p > 0.05), or AM-PAC scores within the first 24 hours (p > 0.05). Conclusion: The control of pain after TKA with a multimodal management protocol is not improved by the addition of LB compared with traditional bupivacaine. Cite this article: Bone Joint J  2021;103-B(6 Supple A):102–107.